Testicular irradiation in childhood lymphoblastic leukaemia. Medical Research Council Working Party on Leukemia in Childhoods. - Eden, O; Lilleyman, J; Richards, S (1990)
The effect of randomly allocated testicular irradiation on the subsequent incidence of testicular infiltration and disease-free survival was assessed in two Medical Research Council Childhood Leukemia Trials. UKALL VI and UKALL VII. None of the 83 boys who actually received testicular radiotherapy subsequently developed gonadal disease. whereas 18 of the 163 who were not irradiated did. Despite this there is no apparent difference in disease-free survival for those randomized to receive testicular irradiation compared to those who were not, after a minimum of 8 years follow up. Although prophylactic testicular irradiation appears to prevent subsequent gonadal relapse there is no evidence that it improves overall prognosis when adequate systemic chemotherapy is used. As it has considerable long-term side effects it cannot be recommended as routine therapy.